Pest categorisation of Bretziella fagacearum. (22nd February 2018) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: Following a request from the European Commission, the EFSA Plant Health (PLH) Panel performed a pest categorisation of Bretziella fagacearum, a well‐defined and distinguishable fungal species of the family Ceratocystidaceae. The species was moved from the genus Ceratocystis to a new genus Bretziella following phylogenetic analysis of the species and its close relatives. The former species name Ceratocystis fagacearum is used in the Council Directive 2000/29/EC. The pathogen is regulated in Annex IAI as a harmful organism whose introduction into the EU is banned. B. fagacearum is only reported from the USA, where it causes a wilt disease on Quercus spp. Other hosts are reported based on inoculation trials, although Chinese chestnut ( Castanea mollissima ) is reported to be naturally infected. No North American oak species has been found to be immune to the disease. The European oak species Quercus robur, Quercus petraea and Quercus pubescens were found to be susceptible in inoculation experiments. The pest could enter the EU via wood (with and without bark, including wood packaging material), plants for planting and cut branches. Hosts and favourable climatic conditions are common in the EU, thus facilitating establishment. The pest would be able to spread following establishment by means of root grafts, insect vectors and movement of wood, plants for planting and other means. The pest introduction would have impacts in woodland and plantations, as oak wilt disease is often lethal in a short period of time. Wood treatment (debarking, kiln drying, fumigation), prompt removal of affected trees and creating root‐free zones between affected and healthy stands are available control measures. The main knowledge gaps concern (i) the survival of the fungus in wood during transport and the association with propagation material, (ii) the presence of suitable vectors in Europe and (iii) the relative susceptibility of the oak species native to Europe under natural conditions. The criteria assessed by the Panel for consideration as a potential quarantine pest are met. For regulated non‐quarantine pests, the criterion on the pest presence in the EU is not met.